A realistic appraisal of the use of embryonic stem cell-based therapies for cardiac repair. (28th November 2019) - Wysoczynski, Marcin; Bolli, Roberto
Abstract: Despite the well-documented capacity of embryonic stem cells (ESCs) to differentiate into cardiomyocytes, transplantation of ESCs or ESC-derived cells is plagued by several formidable problems, including graft rejection, arrhythmias, and potential risk of teratomas. Life-long immunosuppression is a disease in itself. Transplantation of human ESC-derived cells in primates causes life-threatening arrhythmias, and the doses used to show efficacy are not clinically relevant. In contemporary clinical research, the margin of tolerance for such catastrophic effects as malignancies is zero, and although the probability of tumours can be reduced by ESC differentiation, it is unlikely to be completely eliminated, particularly when billions of cells are injected. Although ESCs and ESC-derived cells were touted as capable of long-term regeneration, these cells disappear rapidly after transplantation and there is no evidence of long-term engraftment, let alone regeneration. There is, however, mounting evidence that they act via paracrine mechanisms—just like adult cells. To date, no controlled clinical trial of ESC-derived cells in cardiovascular disease has been conducted or even initiated. In contrast, adult cells have been used in thousands of patients with heart disease, with no significant adverse effects and with results that were sufficiently encouraging to warrant Phase II and III trials. Furthermore, induced pluripotent stem cells offer pluripotency similar to ESCs without the need for lifelong immunosuppression. After two decades, the promise that ESC-derived cells would regenerate dead myocardium has not been fulfilled. The most reasonable interpretation of current data is that ESC-based therapies are not likely to have clinical application for heart disease.